Übungen im Medienrecht - Peifer, Karl-Nikolaus (JURA. Übungen., 2008)
Media law is a portmanteau term for various areas that cover individual and mass communication as information and entertainment media. The aims of this book of exercises are to systematize the individual sections of media law, to demonstrate the interactions with the traditional materials of radio and press law and to work out common structures. The central elements of media law are presented in 12 cases, which are based on current problems.